Characteristics of Academic-Affiliated Health Systems. (April 2020) - Niedzwiecki, Matthew J.; Machta, Rachel M.; Reschovsky, James D.; Furukawa, Michael F.; Rich, Eugene C.
Abstract : Purpose: Changing market forces increasingly are leading academic medical centers (AMCs) to form or join health systems. But it is unclear how this shift is affecting the tripartite academic mission of education, research, and high-quality patient care. To explore this topic, the authors identified and characterized the types of health systems that owned or managed AMCs in the United States in 2016. Method: The authors identified AMCs as any general acute care hospitals that had a resident-to-bed ratio of at least 0.25 and that were affiliated with at least one MD- or DO-granting medical school. Using the Agency for Healthcare Research and Quality 2016 Compendium of U.S. Health Systems, the authors also identified academic-affiliated health systems (AHSs) as those health systems that owned or managed at least one AMC. They compared AMCs and other general acute care hospitals, AHSs and non-AHSs, and AHSs by type of medical school relationship, using health system size, hospital characteristics, undergraduate and graduate medical education characteristics, services provided, and ownership. Results: Health systems owned or managed nearly all AMCs (361, 95.8%). Of the 626 health systems, 230 (36.7%) met the definition of an AHS. Compared with other health systems, AHSs included more hospitals, provided more services, and had a lower ratio of primary care doctors to specialists. Most AHSs (136, 59.1%) had a single, shared medical school relationship, whereas 38 (16.5%) had an exclusive medical school relationship and 56 (24.3%) had multiple medical school relationships. Conclusions: These findings suggest that several distinct types of relationships between AHSs and medical schools exist. The traditional vision of a medical school having an exclusive relationship with a single AHS is no longer prominent. Abstract : Supplemental Digital Content is available in the text.